2022
DOI: 10.1002/smll.202203307
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Enhancing Electrical Conductivity of Pristine Metal–Organic Frameworks for Supercapacitor Applications

Abstract: Metal–organic frameworks (MOFs), known as porous coordination polymers, have attracted intense interest as electrode materials for supercapacitors (SCs) owing to their advantageous features including high surface area, tunable porous structure, structural diversity, etc. However, the insulating nature of most MOFs has impeded their further electrochemical applications. A common solution for this issue is to transform pristine MOFs into more stable and conductive metal compounds/porous carbon materials through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 150 publications
0
30
0
Order By: Relevance
“…Recently, two-dimensional conjugated metal–organic frameworks (2D c -MOFs) have been recognized as an ideal material platform for designing functional porous materials with atomic precision. Their in-plane ring-fused conjugated structures with high electrical conductivities and defined quasi-one-dimensional porous nanochannels with large specific surface areas provide efficient electron/ion transport pathways, making 2D c -MOFs particularly suitable as electrode materials for SCs. Moreover, both aromatic ligands ( e.g. , phthalocyanine and dibenzochrysene) , and square-planar metal coordination linkages ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two-dimensional conjugated metal–organic frameworks (2D c -MOFs) have been recognized as an ideal material platform for designing functional porous materials with atomic precision. Their in-plane ring-fused conjugated structures with high electrical conductivities and defined quasi-one-dimensional porous nanochannels with large specific surface areas provide efficient electron/ion transport pathways, making 2D c -MOFs particularly suitable as electrode materials for SCs. Moreover, both aromatic ligands ( e.g. , phthalocyanine and dibenzochrysene) , and square-planar metal coordination linkages ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The SC using 0.1 M TBAPF 6 is named SS-0.1, while the one using 1 M TBAPF 6 in DCM is named SS-1, respectively. The CV curves of SS-1 [Figure 4A] at different scan rates over a potential window of 0-1.0 V are even closer to a rectangle than the CV curves in a three-electrode system, further confirming the EDLC behaviour of the CsPbBr 3 nanocrystals [10,13] . The shape of the CV is well maintained at a high scan rate of 50 mV s -1 , indicating good rate performance.…”
Section: Electrochemical Performance Characterizationmentioning
confidence: 64%
“…Liu et al used carbon nanotubes wrapped around CsPbBr 3 as the anode of a Li-ion battery, which exhibited a reversible capacity of 644.6 mAh g -1 at a current density of 100 mA g -1 due to the embedded pseudocapacitive behaviour [8] . Further studies have shown that the reduction of Pb 2+ , generating different forms of LiPb alloys, may be responsible for the observed energy storage behaviour, although there are still many open questions regarding the operational mechanism of perovskite electrodes [8][9][10] . Supercapacitors, also called electrochemical capacitors, are a type of energy storage device that is complementary to batteries with distinctive advantages such as much faster charge and discharge rates (higher power density) [11] , outstanding cycling capability and the ability to operate over a broader temperature range [12][13][14] , However, compared to battery research, the study of perovskite in supercapacitors is very rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal–organic frameworks (MOFs) and their composites have been considered as active masses in supercapacitor electrodes [ 239 , 240 , 241 , 242 ]; combined with ICPs, the obtained composites were examined for various electrochemical applications [ 243 ]. The poor electronic conductivity of MOFs was noticed as a major hindrance to their use in a supercapacitor electrode; forming composites [ 156 , 244 , 245 , 246 ], including ICPs, is an obvious solution [ 77 , 242 ]. Only a few experimental observations focused on material science aspects were recorded.…”
Section: The Combinationsmentioning
confidence: 99%